Up with Data Science, and the First Programmer. - Hazzan, Orit; Mike, Koby; Bruderer, Herbert (Communications of the ACM, 2022)
The article presents a couple of blog posts focusing on the topics of machine learning within the context of data science and questions over the identity of the first computer programmer and featured on this journal's website located at https://cacm.acm.org.